Legal sanctions against members of the National Police who Abusing Narcotics at Bengkulu Police Station - Anggi Pratiwi; Jeane Neltje Saly (Pelopor Publikasi Akademika, 2023)
Today narcotics crime is seen as a crime that is an enemy of humanity, therefore countries in the world including Indonesia continue to struggle to eradicate this crime. The issues raised in writing this thesis are Law Enforcement Against Members of the Police Who Abuse Narcotics and Psychotropics, how to regulate and Criminal Sanctions against the National Police who commit Narcotics Crimes, and how to apply criminal sanctions and a code of ethics to the National Police as perpetrators of Narcotics Crimes. The research method used in this paper is the normative juridical research approach. The normative juridical method in which this research examines the literature or secondary data which includes books and legal norms contained in statutory regulations, legal principles, legal rules and legal systematics and also examines the provisions of statutory regulations and legal materials others. From this research it can be concluded that 1) The process of law enforcement against members of the police who are caught in cases of criminal acts of narcotics abuse is in accordance with the applicable laws and regulations, in which in the process all people are equal in the eyes of the law, even in law enforcement the suspects is a member of the police, the sentence can be more severe. This is because the suspect is a law enforcement officer who should carry out a position order to fight narcotics, but the suspect is involved in a criminal case of drug abuse. 2) The process of enforcing the police professional code of ethics against members of the police who are caught in criminal cases of narcotics abuse in fact has not been carried out properly where the police do not immediately take firm action against members who are caught in criminal cases of narcotics abuse, as if the police are still protecting their members and are considered after their members have tried in general court and found guilty of committing a narcotic crime.